Behavioral outcome among survivors of childhood brain tumor: a case control study - Hamidah Alias; Sasirekha Krisnan Morthy; Syed Zulkifli Syed Zakaria; Zulaiha Muda; Azmi Mohd Tamil (BMC, 2020)
Abstract Background Advances in the treatment of childhood brain tumors have significantly improved survival rates. With improved survival rates, long-term treatment-related toxicities have become important, and the resulting complications can affect patients' emotion and behavior. This study aimed to 1) evaluate behavioral outcomes among survivors of childhood brain tumors, 2) compare behavioral outcomes among survivors of childhood brain tumors with survivors of childhood leukemia and healthy children, and 3) determine any demographic, disease, and/or treatment-related factors that could affect the behavioral outcomes of survivors of childhood brain tumors. Methods A comparative cross-sectional study was conducted over a period of 1 year (June 1st, 2018-May 31st, 2019) in two tertiary referral centers in Kuala Lumpur, Malaysia. Thirty-eight survivors of childhood brain tumors aged 6 to 18 years old who had been off-treatment for at least 1 year and were in remission, 38 age- and gender-matched survivors of childhood leukemia who had been off-treatment for at least 1 year and were in remission, and 38 age- and gender-matched unrelated healthy children were recruited. The Child Behaviour Checklist (CBCL) parent report and Youth Self-Report (YSR) questionnaires were used to assess behavioral outcomes. Results Survivors of childhood brain tumors showed statistically significantly worse behavioral outcomes than healthy children for social problems and attention problems (p < 0.05, respectively). A significantly worse outcome was found for "social problems" (p < 0.05) in survivors of childhood brain tumors compared to survivors of childhood leukemia. Significant associations were also found between physical disability, visual impairment, education level of survivors, and father's occupation and behavioral outcomes among survivors of childhood brain tumors. Conclusions Survivors of childhood brain tumors in our center showed poor behavioral outcomes for social problems and attention problems. Thus, effective psychosocial support interventions tailored to individual patients as soon as treatment is completed are important to prevent potentially debilitating emotional problems.